Pilot-scale study of desulfurization wastewater evaporation: Emission and migration characteristics of mercury. (15th September 2022) - Chen, Heng; Zhan, Lingxiao; Gu, Liyan; Zhou, Hao; Feng, Qianyuan; Sun, Zongkang; Wu, Hao; Yang, Linjun
Graphical abstract: Highlights: Fate of Hg is studied on the lab and pilot-scale wastewater evaporation systems. Approximately 93.6% of Hg in the wastewater is firstly released into the gas phase. The released Hg would be further affected by the oxidation and adsorption mechanism. Most of the released Hg(g) is eventually deposited on the solid evaporation product. The leaking risk of the Hg in the final evaporation product should be attended to. Abstract: The hot flue gas evaporation technology exhibited a significant advantage in desulfurization wastewater zero discharge. However, the mercury emission during the wastewater evaporation process was a potential risk that may limit the popularization and application of this technology. The emission and migration characteristics of mercury were studied on the lab-scale furnace and pilot-scale wastewater evaporation system, respectively. The Hg in the wastewater would undergo the release-oxidation/adsorption process. Approximately 93.6% of Hg existing in the wastewater would firstly release due to the high volatility and component of SO3 2− and Cl − . Then, the released Hg would be further affected by the oxidation and adsorption mechanism. The generated HCl gas atmosphere and the active substances in the solid content would oxidize most of the released Hg 0 and lift the Hg 2+ proportion in the flue gas. Besides, the adsorption effect enhanced the conversion from the gaseous Hg to the Hg p, causing a high Hg proportion of 89.4% in the final solid evaporation product. The findings in risk assessment demonstrated that the hot flue gas evaporation technology would not upset the Hg distribution or cause extra Hg emissions for the whole power plant. However, the large water/acid-soluble fraction of Hg in the evaporation product should be considered in the storage and disposal procedure.